The origins of violence : religion, history and genocide - Docker, John. (London : Pluto Press, 2008)
Genocide is commonly understood to be a terrible aberration in human behavior, performed by evil, murderous regimes such as the Nazis and dictators like Suharto and Pinochet. John Docker argues that the roots of genocide go far deeper into human nature than most people realize. Genocide features widely in the Bible, the literature of ancient Greece and Rome, and debates about the Enlightenment. These texts are studied in depth to trace the origins of violence through time and across civilizations. Developing the groundbreaking work of Raphael Lemkin, who invented the term 'genocide', Docker guides us from the dawn of agricultural society, through classical civilization to the present, showing that violence between groups has been integral to all periods of history. This revealing book will be of great interest to those wishing to understand the roots of genocide and why it persists in the modern age.
Genocide as ancient practice : chimpanzees, humans, agricultural society -- Genocide, and questioning of genocide, in the ancient Greek world : Herodotus and Thucydides -- Genocide, trauma and world upside down in ancient Greek tragedy : Aeschylus and Euripides -- Utopia and dystopia : Plato and Cicero's Republics -- Victimology and genocide : the Bible's Exodus, Virgil's Aeneid -- Roman settler imperialism in Britain : narrative and counter-narrative in Tacitus's Agricola and Germania -- The honourable colonizer -- Was enlightenment the origin of the Holocaust? -- Conclusion : can there be an end to violence?
Includes bibliographical references (pages 219-248) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Genocide -- History; Genocide -- Religious aspects -- History; Génocide -- Aspect religieux -- Histoire; SOCIAL SCIENCE -- Demography; HISTORY -- World; Genocide; Genocide -- Religious aspects; Völkermord; Geschichte; History